Health Assistance on Meeting Basic Human Needs (Sleep Rest, Activity) For Quran Memorizing Female Students at PPTQ Muhammadiyah Bani Husein - Kalipepe Yosowilangun In 2023: Pendampingan Kesehatan Tentang Pemenuhan Kebutuhan Dasar Manusia (Istirahat Tidur, Aktivitas) Pada Siswi Tahfidz Quran Di PPTQ Muhammadiyah Bani Husein - Kalipepe Yosowilangun Tahun 2023 (JURNAL UNEJ, 2024)
The health mentoring activity on fulfilling basic human needs (sleep and activity) for Quran Tahfidz students at PPTQ Muhammadiyah Bani Husein - Kalipepe, Yosowilangun, was conducted to increase participants' knowledge and awareness about the importance of adequate sleep, physical activity, and the use of herbal remedies as natural solutions. This activity consisted of an initial assessment (pre-test), material presentation, and a final assessment (post-test). The pre-test results showed that most participants had limited knowledge about basic human needs. After presenting the material using interactive lectures and media such as PowerPoint and X Banners, the post-test results indicated a significant increase in participants' understanding. The material covered the importance of adequate sleep, physical activity, and herbs that can be used to address sleep disorders, such as pandan, lavender, jasmine, ginseng, nutmeg, and green tea. This knowledge improvement aligns with Maslow's theory on fulfilling basic physiological needs. The results of this activity demonstrate that health education conducted with appropriate methods and supported by effective media can positively impact the increase of knowledge and community health. The authors thank the parties who supported this activity and declare no conflict of interest in the implementation of this community service activity. **Keywords:** health mentoring, basic human needs, sleep, activity, herbal remedies, PPTQ Muhammadiyah Bani Husein